Ensino da Ecologia mediado por simulação computacional da Cadeia Alimentar - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
This dissertation presents the application of a computer simulation model to minimize the difficulties of the teaching and learning process of teaching Ecology from the use of a computational model of the food chain. The goal is to analyze the construction of new concepts on the food chain in the face of the equilibration process using a computational model. To describe the dynamics of biological systems, a computer simulation program was developed based on the Lotka-Volterra prey-predator model. The result is the construction of new concepts by the student from the analysis of the responses of experiments and virtual situations. The pedagogical approach is developed based on the constructivism of Jean Piaget. In this perspective, the simulation model presents itself as an instrument to support the teaching of Ecology, helping to learn new concepts. The research instruments, the organization and categorization of data, favored discursive aspects, referring to the students` responses, following the guidelines of Bardin (2011). The place of study was a municipal elementary school, with 6th grade students, from the city of Manaus / Am. Based on the results obtained, it was realized that the simulation contributes to the construction of knowledge and provides good support for learning.
Keywords: Cadeias alimentares (Ecologia); Ecologia animal - Estudo e ensino (Ensino fundamental); CIÊNCIAS BIOLOGICAS; Ensino de Ecologia; Equilibração; Cadeia Alimentar; Simulação Computacional